1958
DOI: 10.2337/diab.7.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triglycerides in Health and Diabetes

Abstract: The historical observation that individuals with uncontrolled diabetes may have high concentrations of serum lipids and may also have an increased incidence of arteriosclerosis has much to do with the presentday theories relating serum lipids and arteriosclerosis. The fact that the lipemia of diabetes is related to defective carbohydrate metabolism rather than to fat in the diet is often overlooked in incrimination of dietary fat. This Symposium offers an opportunity to discuss factors other than dietary fat w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1959
1959
1975
1975

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Hypertriglyceridemia of varying degrees is frequently seen in untreated diabetes mellitus; it is almost the rule in severe insulin deficiency with ketoacidosis (19)(20)(21)(22). Treatment with insulin or oral antidiabetic agents returns elevated plasma TG to or toward normal indicating that absolute or relative lack of endogenous insulin may be a cause of diabetic hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%
“…Hypertriglyceridemia of varying degrees is frequently seen in untreated diabetes mellitus; it is almost the rule in severe insulin deficiency with ketoacidosis (19)(20)(21)(22). Treatment with insulin or oral antidiabetic agents returns elevated plasma TG to or toward normal indicating that absolute or relative lack of endogenous insulin may be a cause of diabetic hypertriglyceridemia.…”
Section: Introductionmentioning
confidence: 99%
“…The changes described here must be distinguished from the changes accompanying normal alimentary lipemia characterized by a small rise in triglyceride concentration restricted to the lipoproteins of D < 1.019 (19,20), although an increase in the chylomicron cholesterol and an associated decrease in the cholesterol of the remaining serum may occur during the intravenous infusion of fat emulsions (21) in association with a much greater increase in triglyceride concentration than usually occurs after a fat meal.…”
Section: Discussionmentioning
confidence: 99%
“…The response is even greater in patients with coronary disease. This fact corresponds to the observation of Albrink and Man (19), Kagan et al (20) and Albrink (21) that plasma triglyceride levels are higher in old people than in younger persons. Kaufmann (22) and Nikkila and Niemi (23) reported that the activity of LPL decreases with age.…”
Section: The Biological Premisesmentioning
confidence: 99%